Benefits and disadvantages of implementing the electronic patient record for the health service (Research, Society and Development, 2020)
This is a literature search with a qualitative approach and descriptive character with the objective of identifying the benefits and disadvantages found in the implementation of Electronic Patient Records in the health service. As a methodology, the data were collected in a Virtual Database. For this purpose, the VHL was used, in the following LILACS, MEDLINE, BDENF Information Bases and by the scholar.google.com.br email address, in the period of May 2019. As a result, advantages were found, such as agility in accessing related information to the patient, simultaneous use of medical records, readability, elimination of data redundancy, systematized organization and also disadvantages such as major investments in hardware, software and training, resistance by health professionals and slow and inoperable systems. It is concluded that, for the implementation of the PEP, the standardization of medical records, the establishment of team information flowcharts, the training of all involved and the control and evaluation of results must be considered.